Association Between Environmental ConditionsPersonal Hygiene Sanitation of Mother and Diarrhea Incident in Children at Working of Area Health Watukumpul District Pemalang - Prabhastyan Azmy (Jurnal Kesehatan Masyarakat (Undip), 2015)
Diarrheal diseaseis one of theenvironmentally–based contagious diseasethatis still amajor problemindeveloping countries, including inIndonesia. Number of patients withdiarrhea in children under five year oldin SubWatukumpulin 2012amounted to1,340cases.The purposeofthis researchwas to determinethe assosiationbetweenenvironmental sanitationandpersonal hygieneto mothers withthe incidence of diarrheain children under five year old inthe Work AreaHealth CenterWatukumpulDistrict Pemalang. This is anobservational studywith cross sectional approach. The populationin this study werechildren aged0months-59 monthswith a total of5250children under five year old. Samplesweretakenat 94children under five year oldusingproportional randomsamplingmethod. Data analysisusing Chi square testwith a significance levelα=5%. The results ofthis study indicate thatforrespondents whodo notqualifyforcleanwater supplyfacility conditions32(34%), the condition oflatrines31(33%), the conditionSPAL66(70.2%), the condition ofTPS64(67), the practice ofpersonalmaternalhygieneorhand washingbeforefeedingtoddlers34(38.2%), motherswash their handsafter defecating28(29.8%), and managingfood27(28.7%). The results ofthe analysis ofthe assosiationof each independent variablewithdiarrheafollowing: cleanwater supplyfacility conditions(p =0.044), the condition oflatrines(p =0.980), SPALconditions(p =0.645), condition ofwaste disposal (p =0.626), WashhandsBeforeEatingOrFeedingToddlers(p =0.065), washinghandsafter defecation(p =0.333), ManagingFood(p =0.195). This studycan beconcluded that there isaassosiation betweenthe conditionmeanswater providerswith theincidence of diarrhea inchildren under five year old inthe Work AreaHealth CenterWatukumpulDistrict Pemalang